Keperluan modal bank, risiko dan pemamahan kredit : Pendekatan persamaan serentak - Ismail, Abd Ghafar; Goh, Chuan Hai (Universiti Utara Malaysia, 2000)
The purpose of this research is to analyze the effects of Basle accord on the three main issues: a) does the introduction of fixed minimum capital requirements lead banks to hold higher capital ratio? b) do the banks adjust their capital and risk level to achieve regulatory and market capital requirements? c) do the changes in the capital ratios or risk level create credit crunches which affect the economic growth? To address these issues, an econometric model, which apply the 3SLS method is developed in order to identify the factors, which affects the capital ratio, risk and credit crunch. In addition, a simulation is done to examine the counterfactual of several variables. Descriptive analyses find that all commercial banks in Malaysia have already achieved the regulatory minimum capital requirement of 8%. The findings also show that an increase in the capital ratio creates credit crunch.